Talent Management and Performance of Manufacturing Firms in Nigeria - Nicholas Ngozi Igwe; Chukwuebuka Ugonna Obidigbo; Patrick Obumneme Dulora (Innovation Business Management and Accounting Journal, 2025)
This study examined the nature of the relationship that exists between talent management and organizational performance in selected manufacturing firms in Anambra State, Nigeria. The study was anchored on Resource Based Theory (RBT). The research used the cross-sectional research design to plan for the study. The population of the study stood at three hundred and twenty (320) workers selected from different departments in the organizations. The sample size was one hundred and twenty three (123) workers which was arrived at using Taro Yamane (1967) formula. Data were collected using structured questionnaire from the random sampled workers of the selected manufacturing firms in Anambra State. The reliability of the measuring instrument was tested using Cronbach Alpha. The data were presented using descriptive statistics and Pearson correlational analysis was used in testing the hypotheses. The study revealed that there was a positive significant relationship between the dimensions of talent management (talent attraction, talent development, talent retention) on organizational performance dimensions (job satisfaction, employee loyalty, and employee commitment) respectively. The study concluded that manufacturing firms which have the capacity and resources to attract talents tends to guarantee employee job satisfaction more than those which lack the required resources. The study recommended that manufacturing firms should exhibit objectivity in recruitment process, offer the right reward, provide job security, and invest in staff welfare so as to increase the chances of attracting highly talented employees.